2020
DOI: 10.1002/spe.2837
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic resource provisioning for multilayer cloud applications with K‐nearest neighbor resource scaling and priority‐based resource allocation

Abstract: SummaryProviding a pool of various resources and services to customers on the Internet in exchanging money has made cloud computing as one of the most popular technologies. Management of the provided resources and services at the lowest cost and maximum profit is a crucial issue for cloud providers. Thus, cloud providers proceed to auto‐scale the computing resources according to the users' requests in order to minimize the operational costs. Therefore, the required time and costs to scale‐up and down computing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Take the L i − 1 and R i − 1 of the previous round as the input of the next round, and the iteration rule of L i and R i of the output bits is 16). Here, f is a permutation function [17], which includes E change, S and P transformation, e ⊕ symbol indicates XOR. Step 3: Finally, the ciphertext y is obtained by reversing the IP −1 table.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Take the L i − 1 and R i − 1 of the previous round as the input of the next round, and the iteration rule of L i and R i of the output bits is 16). Here, f is a permutation function [17], which includes E change, S and P transformation, e ⊕ symbol indicates XOR. Step 3: Finally, the ciphertext y is obtained by reversing the IP −1 table.…”
Section: Methodsmentioning
confidence: 99%
“…Dakhil et al task digital twins to update building information models in near real-time using IoT sensors, while blockchain authenticates and increases confidence in all data transactions of digital twins [16]. Mazidi et al found that the scalability nature of cloud computing attracted application service providers (ASPs) to use cloud application hosting [17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…For multilayer applications of cloud computing, an autonomic resource provisioning method is described in Reference 35. In this method, k-nearest neighbor (KNN) approach is used for analyzing and labeling VMs, and statistical approach is used for making scaling decisions.…”
Section: Autonomic Resource Managementmentioning
confidence: 99%
“…With the development of the theory of machine learning, machine learning methods become more and more attractive in the field of cloud computing. Mazidi et al [9] propose a new method based on the K-nearest neighbor algorithm that is used to analyze and label virtual machines, and statistical methods are used to make expansion decisions. Wei et al [10] propose a cloud application auto scaling approach based on Q-learning method to help SaaS providers make optimal resource allocation decisions in a dynamic and stochastic cloud environment.…”
Section: Related Workmentioning
confidence: 99%